O direito humano à oportunidade - Vilhena, Josimary Rocha de (2016)
The Universal Declaration of Human Rights - an historic document which to this day is considered the foundation of human rights proclaimed on December 10, 1948 states, in several passages, that all people have equal rights safeguarding all proportions and that the State is incumbent to take effect without making distinctions. Since then, the world has a new vision, turning the human being as the center and the rights-object, a right set towards general clauses and collective principles in which the "thing" protected is replaced by "someone" legally safeguarded .With the recognition that the dignity is "inherent to all members of the human family" and that the personality rights are inalienable, the Declaration states that this is the foundation of "freedom, justice and peace in the world." In 1948 the American Declaration of Human rights and duties was also proclaimed in Bogotá, targeting a range of rights and stating that the human being needs "equality of opportunity in all cases according to the natural talents, merit and the desire to utilize the resources that can provide the community and the State." This is the focus of this study: the human right to equality of opportunity as an implementation mechanism of the inalienable rights of humanity